2002
DOI: 10.1139/t01-082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fines content and initial shear stress on dynamic properties of hydraulic reclaimed soil

Abstract: The hydraulic placement of sand fill is one of the most important methods of land reclamation. During the reclamation process, losses of fines in sand are induced by the transportation of soil which affects the dynamic properties of the soil materials. In this study, the reclaimed soil in the Yunlin area of Taiwan is adopted as the test material. Different fines contents, different relative densities, and initial stress ratio were taken as test conditions. Resonant column tests were performed to evaluate the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(9 citation statements)
references
References 2 publications
1
7
1
Order By: Relevance
“…Given that both Ottawa sand and silica fines are hard grained materials and given the range of confining pressure applied, the value of 0•809 appears to be unusually high compared with the reported values in the literature. Moreover, a dramatic variation in the stress exponent does not appear to be in agreement with the observations of Iwasaki & Tatsuoka (1977) and Chien & Oh (2002) that the stress exponent is insensitive to the presence of fines.…”
Section: Introductioncontrasting
confidence: 51%
“…Given that both Ottawa sand and silica fines are hard grained materials and given the range of confining pressure applied, the value of 0•809 appears to be unusually high compared with the reported values in the literature. Moreover, a dramatic variation in the stress exponent does not appear to be in agreement with the observations of Iwasaki & Tatsuoka (1977) and Chien & Oh (2002) that the stress exponent is insensitive to the presence of fines.…”
Section: Introductioncontrasting
confidence: 51%
“…The pronounced effect of q/p on G can be observed up to c \ 10 -1 %. However, for c [ 10 -1 %, q/p has an insignificant influence on G. In addition, G max is observed to be higher for q/p = 0.6 assembly when compared to q/p = 0 assembly (Chien and Oh 2002). The higher value of G max for q/p = 0.6 may be due the higher mean stress along the major principal stress direction.…”
Section: Effect Of Gradationmentioning
confidence: 90%
“…This has compelled many researchers to investigate this aspect more rigorously. Singh (1994) and Chien and Oh (2002) reported that the strength of a specimen decreases with increase in silt content at a given relative density. However, Polito and Martin (2001) reported that the strength of a specimen remains relatively constant with increase in silt content up to the limiting silt content, and then there is a drastic fall in cyclic resistance down to a stable level with increase in silt content till pure silt.…”
Section: Constant Relative Density Approachmentioning
confidence: 99%